Effect of Feed Restriction and Garlic Supplementation on Growth Performance, Nutrient Utilization and Meat Quality in Female Broiler’s Performance - Singh, Vishavdeep; Singh, Udeybir; Sethi, A. P.S. (Indian Journal of Animal Nutrition, 2020)
An experiment was conducted to study the effects of feed restriction and garlic supplementation on growth performance, nutrient utilization and meat quality in female broilers. In this study, 120, day-old female broilers were randomly distributed into 5 treatment groups each having 4 replicates with 6 birds in each replicate. Diets were formulated as per ICAR 2013 specifications and were fed in 3 phases. Treatment T1 served as control. The other treatments comprised: T2=T1 with feed restriction (10-12 h) at 8-17 days of age (DOA) with garlic supplementation, T3=T1 with feed restriction at 8-17 DOA (10-12 h) without garlic supplementation, T4=T1 with feed restriction at 18-27 DOA (10-12 h) with garlic supplementation, T5=T1 with feed restriction at 18-27 DOA (10-12 h) without garlic supplementation. Early feed restriction (8-17 DOA) without garlic supplementation reduced (P